Temporal distribution of gastroenteritis viruses in Ouagadougou, Burkina Faso: seasonality of rotavirus - Ouedraogo, Nafissatou (BMC Public Health, 2017)
BACKGROUND: Acute gastroenteritis is one of the most common diseases among children and adults, and continues to cause a major problem of public health in Burkina Faso. The temporal pattern of rotavirus, norovirus, sapovirus, astrovirus, adenovirus and Aichivirus A was studied by examining prevalence of gastroenteritis viruses in association with meteorological variables in Ouagadougou, Burkina Faso. METHODS: Stool samples from 263 children under 5 years of age and 170 older children patients, adolescent and adults with gastroenteritis were collected in Ouagadougou, Burkina Faso from November 2011 to September 2012. Enteric viruses were detected using real-time or end-point (RT-) PCR. Temperature, humidity and monthly rainfall were recorded from the National Meteorological Direction. Categorical data were compared by Chi-square tests and the effect of weather variables and monthly prevalence were analyzed using Pearson Correlation Coefficient test. RESULTS: The prevalence of rotavirus infections was significantly higher in the dry season (Season S1) compared to the wet season (season S2) (p = 0.03) among the population of children under 5 years of age. No statistically significant difference was observed regarding other gastroenteritis viruses comparing the dry season and the wet season. Positive cases of rotavirus, norovirus, adenovirus and sapovirus in children under 5 years of age were correlated with temperature (r = −0.68, p = 0.01; r = −0.74, p < 0.001; r = −0.68, p = 0.01; r = −0.65, p = 0.02, respectively) and only rotavirus, adenovirus and astrovirus were correlated with relative humidity (r = −0.61, p = 0.04; r = −0.54, p = 0.08; r = −0.51, p = 0.1 respectively). No correlation was observed with rainfall. In older children, adolescent and adults patients, rotavirus and norovirus correlated with relative humidity (r = −0.58, p = 0.05; r = 0.54, p = 0.08 respectively), but, no correlation was observed between the temperature and the rainfall. CONCLUSION: This study extends knowledge on the monthly fluctuations on the prevalence of viral gastroenteritis. These results can provide valuable information necessary to alert health care providers when a period of infection in the community is likely to occur. The transmission of these viruses in Burkina Faso could depends on multiple factors including climatic variables.